Assistance in Developing Numeracy Problems as Learning Assessments - Amelia, Sindi; Alzaber, Alzaber; Shalawati, Shalawati (Universitas Pahlawan Tuanku Tambusai, 2024)
Improving numeracy skills is essential, given that Indonesian students’ numeracy achievements are still below standard. The Kurikulum Merdeka includes three types of assessments—Diagnostic Assessment, Formative Assessment, and Summative Assessment—forming a comprehensive series in the classroom learning process. These assessments provide an opportunity to enhance students' numeracy skills. Therefore, teachers must develop numeracy question to evaluate the learning process. SDIP YLPI, an active partner of the Mathematics Education Study Programme at Universitas Islam Riau, requires assistance in creating numeracy questions for the Kurikulum Merdeka. This community service aims to provide intensive assistance to classroom teachers at SDIP YLPI in preparing numeracy questions as learning assessments in the Kurikulum Merdeka. The activity began with the preparation of standard questions, which were then transformed into numeracy questions by focusing on the stimulus and its components. As a result of this community service, participants have successfully formulated two numeracy questions script for level 3 (grades 5-6). The questions in this assessment focus on the theme of numbers within a personal context, with an emphasis on ensuring a cognitive level of understanding. The format chosen for this assessment is multiple-choice, featuring true/false options.